Adaptive attack-free protocol for consensus tracking with pure relative output information. (July 2020) - Lv, Yuezu; Wen, Guanghui; Huang, Tingwen; Duan, Zhisheng
Abstract: This paper considers fully distributed adaptive protocol design for cooperative tracking problem based only on pure relative output information. To tackle leader's trajectory in the presence of unknown control input, most of the existing observer-based protocols are designed based on absolute output information as well as the relative observer information among neighboring agents, which would suffer from potential network attack. To conquer such limitation, the definition of attack-free protocol is proposed, where no communication information exchange is allowed among neighboring agents, but only relative output measurement can be available. In this setting, the protocol is born to be free from network attack. By taking leader's control input as external disturbance for each agent, some new kinds of full-order and reduced-order disturbance separation observers are introduced to achieve observation of consensus error. Based on such observer design methods, fully distributed adaptive protocols are successfully proposed to realize distributed tracking without using any absolute output information nor the spectrum information of the graph. Another favorable property of the protocols lies in the communication burden reduction, since to obtain the attack-free feature, each agent does not communicate its designed observer with its neighbors. The effectiveness of the proposed protocols are verified by numerical simulations on a group of transport aircrafts with short-period dynamics.